From the Desert: the erosive forces of Fiction in Ciencias morales (Martín Kohan) and La mirada invisible (Diego Lerman) (Anclajes, 2012)
The novel Ciencias Morales (2007), by Martín Kohan, narrates life at Colegio Nacional de Buenos Aires during Malvinas’ War. A meticulous and precise story reproduces the ambition of total control and the oppressive atmosphere inside the school. A series of silences and ambiguities, though, reveal the impossibility of such control and its illusory narration. Even when it’s not named straight, war structures and goes through the whole novel.  In this work we analyze  the senses that Ciencias morales produces regarding war and the transformations on them that take place in the film La Mirada Invisible (2010), by Diego Lerman. The aim is to research into the way in which some fictions of the 21st century put themselves according to state stories linked to biopower- as defined by Michel Foucault- to narrate the recent past: dictatorship, war and the link between them.
Keywords: Malvinas' war; Kohan; fiction; control; resistance